2003
DOI: 10.3758/bf03196515
|View full text |Cite
|
Sign up to set email alerts
|

A relevance theory of induction

Abstract: One of the central functions of categorization is to support reasoning. Having categorized some entity as a bird, one may predict with reasonable confidence that it builds a nest, sings, and can fly, though none of these inferences is certain. In addition, between-category relations may guide reasoning. For example, from the knowledge that robins have some enzyme in their blood, one is likely to be more confident that sparrows also have this enzyme than that raccoons have this enzyme. The basis for this confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
278
9
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(300 citation statements)
references
References 29 publications
11
278
9
2
Order By: Relevance
“…These limitations include the models' inability to incorporate the influence of different predicates (Heit & Rubinstein, 1994), background knowledge of an examiner (Proffitt et al, 2000), and complex reasoning skills that an examiner applies (Heit, 2000;Medin et al, 2003). The present study extends these findings by documenting that categorical information by itself could modify participants' inductive judgments beyond general similarity information.…”
Section: Implications and Extensionsmentioning
confidence: 52%
See 1 more Smart Citation
“…These limitations include the models' inability to incorporate the influence of different predicates (Heit & Rubinstein, 1994), background knowledge of an examiner (Proffitt et al, 2000), and complex reasoning skills that an examiner applies (Heit, 2000;Medin et al, 2003). The present study extends these findings by documenting that categorical information by itself could modify participants' inductive judgments beyond general similarity information.…”
Section: Implications and Extensionsmentioning
confidence: 52%
“…In a typical task, participants are given premises, such as All grizzly bears have Disease X and All polar bears have Disease X, and participants judge the strength of a conclusion such as All bears have Disease X (Heit, 2000;Heit & Rubinstein, 1994;Medin, Coley, Storms, & Hayes, 2003;Osherson et al, 1990;Osherson et al, 1991;Rips, 1975;Sloman, 1993).…”
Section: Definition and Two Types Of Categorical Induction Tasksmentioning
confidence: 99%
“…Gelman & Markman, 1986;Heit & Rubinstein, 1994;Shafto & Coley, 2003;Medin et al, 2005 Like all of our models, the causal model relies on a structure and a stochastic process. The structure captures knowledge about predator-prey relationships among a group of species.…”
Section: Causal Reasoningmentioning
confidence: 99%
“…"has a liver with two chambers that act as one") people draw upon taxonomic knowledge about animals to guide inferences, but when reasoning about behavioral properties (e.g. "usually travels in a back-and-forth, or zig-zag, trajectory") people draw upon ecological knowledge (see also Medin, Coley, Storms, & Hayes, 2003;Shafto & Coley, 2003). Barsalou (1983) demonstrated that people derive cross-cutting categories, such as 'things to take out of the house in case of a fire', in the service of goals, and that these goal-based categories are used in planning (Barsalou, 1991).…”
mentioning
confidence: 99%